Ruang Bagi Pekerja Perempuan: Responsivitas Gender di Tempat Kerja - Ramdlan, Asep; Barliana, Mokhamad Syaom (Universitas Batanghari Jambi, 2024)
Cases of violence and harassment in the workplace still occur quite frequently, especially experienced by female workers. The results of the ILO survey provide figures that illustrate that the protection of morals and decency is still not optimal, even though many regulations and guidelines related to worker protection have been issued. Among the efforts to prevent violence and harassment that can be done is to provide spaces for female workers in the workplace. Providing space for female workers not only provides comfort in working, but can also result in productive work. In this article, several literatures are reviewed which show that providing spaces for female workers plays a role in protecting workers' rights, especially regarding the protection of morals and decency. The literature studied includes regulations, books, journals, research results and articles on the internet. This article describes workers' rights that must be protected, various violations of morals and decency that often occur, as well as efforts to prevent these violations. It is hoped that this study will provide an explanation regarding the need for space for female workers in the workplace in providing protection for the rights of female workers. These spaces include a comfortable and safe work space, changing room, toilet, rest room and lactation room.